Pemanfaatan Limbah Kotoran Sapi dan Kulit Durian Menjadi Bio-briket - Widy, Widy; Saade, Aminuddin; Faradila, Soraya (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Indonesia has great potential in the livestock sector that produces livestock waste. Utilization of this waste as a raw material for bio-briquettes can be an alternative sustainable energy solution. This study aims to examine the utilization of waste from cow dung and durian peel into bio-briquettes and analyze the resulting water content, ash content, and calorific value. This study was conducted in Ujung Lamuru Village, Lappariaja District, Bone Regency, in March-April 2025. The method used was a Completely Randomized Design (CRD) with 4 treatments and 4 replications. The results showed variations in water content, ash, and calorific value according to the composition of the material. The lowest water content was in P0 (12.2%), the highest water content was in P2 treatment (38.9%), the lowest ash content was in P0 (49.1%), the highest ash content was in P2 (70.2%), and the highest calorific value was in P3 (2116.75 cal/g), and the lowest calorific value was in P0 (1556.5). All parameters differed significantly between treatments, but did not meet SNI No. 1/6235/2000. The composition of the raw materials significantly influenced the quality of the bio-briquettes, including moisture content, ash content, and calorific value. The best treatment for moisture and ash content was P1 (90% cow dung charcoal and 5% tapioca flour), while the highest calorific value was obtained from P3 (60% cow dung charcoal, 35% durian peel charcoal, and 5% tapioca flour). The balance of raw material and adhesive proportions is a key factor in developing efficient and environmentally friendly bio-briquettes.